SISTEM INFORMASI AKUNTANSI PENGOLAHAN DANA KAS KECIL MENGGUNAKAN METODE IMPREST PADA PT SINAR SOSRO BANDARLAMPUNG - Dedi Darwis; Dini Wahyuni; Dartono Dartono (Universitas Teknokrat Indonesia, 2020)
PT Sinar Sosro Bandar Lampung is a company engaged in the sale of beverages. Data processing at PT Sinar Sosro issuance of claim evidence is still manual, which has not been computerized, one of which is the process of issuing the calculation of claim evidence to the company. Based on the above problems, there are several solutions to deal with so that the management of petty cash funds can simplify spending. The design of the information system for managing petty cash funds uses the imprest method at PT Sinar Sosro Bandar Lampung, namely the design of the system is done using Use Case Diagrams and Applications are built using Borland Delphi 7 and MySQL databases. Testing this system uses a black box. The results of this study are to produce a petty cash fund management information system containing information about the expenditure of petty cash funds, proof of claims that can help and be evidence of the existence of expenditure activities carried out when the petitioner wants to use petty cash funds.